2021
DOI: 10.1002/qua.26870
|View full text |Cite
|
Sign up to set email alerts
|

Molecular representations for machine learning applications in chemistry

Abstract: Machine learning (ML) methods enable computers to address problems by learning from existing data. Such applications are becoming commonplace in molecular sciences. Interest in applying ML techniques across chemical compound space, from predicting properties to designing molecules and materials is in the surge. Especially, ML models have started to accelerate computational chemistry, and are often as accurate as state‐of‐the‐art electronic/atomistic models. Being an integral part of the ML architecture, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 219 publications
0
27
0
Order By: Relevance
“…However, when we would have data from multiple molecules, we would not necessarily need to restrict ourselves to the input features used in this work. We can choose from a zoo of molecule featurization techniques developed in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…However, when we would have data from multiple molecules, we would not necessarily need to restrict ourselves to the input features used in this work. We can choose from a zoo of molecule featurization techniques developed in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…To convert API and excipient molecules into computer-readable formats, multiple molecular representation methods, including extended-connectivity fingerprints (ECFP) and 2D molecular descriptors, were applied ( Jiang et al, 2022 ). Molecular descriptors contained physical and chemical properties of the APIs and excipients were generated by computer ( Raghunathan and Priyakumar, 2022 ). Some published literature compared the model's predictive performance using different molecular representation methods and found that ECFP-based models outperformed 2D molecular descriptors-based ones ( Dong et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is generally done in the form of atomic environment vectors (AEVs), which contain the desired information in a computer-understandable manner. Thus, a lot of effort has been made in recent years within the scientific community to develop suitable featurization approaches 100,101 such as the Bag of Bonds scheme, 36 Coulomb matrices, 46,102 Atom Centered Symmetry Functions (ACSF), 103,104 along with its many different flavors, [105][106][107] or the more recent Gaussian moments, 108 which would ultimately allow for the construction of reliable ML approaches. Despite being rigorous and useful, most strategies still recover little to no information about the actual chemistry, and are usually focused on encoding the radial and angular environments and the chemical composition of the system, just to mimic the external potential without further chemical insight.…”
Section: Electron Density Descriptors In Machine Learningmentioning
confidence: 99%